The Progressive Development Of Multifunctional Composite Materials In Different Applications - Muhammad Akhsin Muflikhun (Institut Teknologi Dirgantara Adisutjipto, 2020)
Composite materials gain huge interest from researchers due to its advantages and flexibility. Strength and properties that can be adjusted based on the needs and applications is a specific advantage of composite materials. Since these advantages can be applied in many fields, composite materials often clustered in multifunctional materials. This study aims to lists and classified the progressive development of multifunctional composite materials that found and already proven can be applied in many applications. This study also gives data that can be driven to readers from different backgrounds and used it for further purposes. The results are shown that the progressive development of multifunctional composite materials not only one step forward in the technical achievements but also the energy and environment-related to human ecosystems.